Nuclear Anomolies In Exfoliated Buccal Cells Of Occupationally Lead Exposed Population - K.RUDRAMA DEVI; D.MADHAVI; J.KARUNA KUMARI. (International Journal of Pharma and Bio Sciences, 2011)
Lead (Pb), a toxic contaminant metal used in many important industrial processes, is widely used in batteries, paint vanishes, in pipe covering and in welding. The exposure showed a high risk of human health and development of several types of cancers. A total of 64 male workers in Hyderabad battery unit in Mahaboobnagar District, Andhra Pradesh were investigated for genetic damage in buccal cells of exposed and control subjects. A questionnaire based survey was conducted and buccal smears were conducted from oral cavity and analyzed for nuclear anomalies. A high frequency of Karyolysis was observed among male workers. The percentage of nuclear anomalies was observed in workers inhaled lead oxide fumes in Industrial atmosphere. The habit of smoking enhanced the frequency of micronuclei in buccal cells when compared with controls. The present study clearly reveals the mutagenic nature in occupational exposure to lead.